In Vitro Assembly of the T=13 Procapsid of Bacteriophage T5 with Its Scaffolding Domain - Huet, Alexis (American Society for Microbiology (ASM), 2010)
The Siphoviridae coliphage T5 differs from other members of this family by the size of its genome (121 kbp) and by its large icosahedral capsid (90 nm), which is organized with T=13 geometry. T5 does not encode a separate scaffolding protein, but its head protein, pb8, contains a 159-residue aminoterminal scaffolding domain (Δ domain) that is the mature capsid. We have deciphered the early events of T5 shell assembly starting from purified pb8 with its Δ domain (pb8p). The self assembly of pb8p is regulated by salt conditions and leads to structures with distinct morphologies. Expanded tubes are formed in the presence of NaCl, whereas Ca(2+) promotes the association of pb8p into contracted tubes and procapsids. Procapsids display an angular organization and 20-nm-long internal radial structures identified as the Δ domain. The T5 head maturation protease pb11 specifically cleaves the Δ domain of contracted and expanded tubes. Ca(2+) is not required for proteolytic activity but for the organization of the Δ domain. Taken together, these data indicate that pb8p carries all of the information in its primary sequence to assemble in vitro without the requirement of the portal and accessory proteins. Furthermore, Ca(2+) plays a key role in introducing the conformational diversity that permits the formation of a stable procapsid. Phage T5 is the first example of a viral capsid consisting of quasi-equivalent hexamers and pentamers whose assembly can be carried out in vitro, starting from the major head protein with its scaffolding domain, and whose endpoint is an icosahedral T=13 particle.